The MEDEA FAR-EAST Study: Conceptual framework, methods and first findings of a multicenter cross-sectional observational study - Hoschar, Sophia (BMC Emerg Med, 2019)
BACKGROUND: The substantial increase in cardiovascular diseases (CVD) in China over the last three decades warrants comprehensive preventive primary and secondary strategies. Prolonged prehospital delay (PHD) has been identified as a substantial barrier to timely therapeutic interventions for acute myocardial infarction (AMI). Despite worldwide efforts to decrease the patient’s decision-making time, minimal change has been achieved so far. Here, we aim to describe the conceptual framework and methods and outline key data of the MEDEA FAR-EAST Study, which aimed to elucidate in-depth barriers contributing to delay in Chinese AMI-patients. METHODS: Data sources of this multicenter cross-sectional observational study are a standardized bedside interview, a self-administered tailored questionnaire tool and the patient chart. PHD was defined as the main outcome and triangulated at bedside. Standard operation procedures ensured uniform data collection by trained study personnel. The study was ethically approved by Tongji-Hospital and applied to all participating hospitals. RESULTS: Among 379 consecutively screened patients, 296 (78.1%) fulfilled eligibility criteria. A total of 241 (81.4%) AMI-patients were male and 55 (18.6%) female. Mean age was 62.9 years. Prehospital delay time was assessed for 294 (99.3%) patients. Overall median PHD was 151 min with no significant sex difference. Symptom mismatch was present in 200 (69.7%) patients and 106 (39.0%) patients did not attribute their symptoms to cardiac origin. A total of 33 (12.4%) patients suffered from depression, 31 (11.7%) from anxiety and 141 (53.2%) patients employed denial as their major coping style. CONCLUSION: This is the first study on prehospital delay with emphasis on psychological variables in Chinese AMI-patients. A comprehensive assessment tool to measure clinical and psychological factors was successfully implemented. Socio-demographic key data proved a good fit into preexisting Chinese literature. Potential barriers including cardiac denial and symptom-mismatch were assessed for the first time in Chinese AMI-patients. The pretested selection of instruments allows future in depth investigations into barriers to delay of Chinese AMI-patients and enables inter-cultural comparisons.